2020
DOI: 10.1016/j.heliyon.2020.e04746
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial psychometric properties of a panic buying scale during COVID-19 pandemic

Abstract: Fear is a powerful driver of human behavior, even more during times of crisis. Panic buying occurs when fear and panic influence behavior leading people to buy more things than usual. So far, no specific scale on this has been found in the major databases, thus the aim of this exploratory study is to develop a Panic Buying Scale (PBS) during COVID-19 pandemic. 393 Brazilians took part in this study (251 women and 142 men), answering a sociodemographic questionnaire and instruments of these variables: (1)panic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(152 citation statements)
references
References 35 publications
3
136
2
11
Order By: Relevance
“…However, negative emotions such as fear or worry could also have negative consequences in case of dealing with a disaster. For example, previous research indicated that people experiencing fear and uncertainty (such as COVID-19 outbreak) tend to buy more things than usual (i.e., panic buying, Arafat et al, 2020;Lins and Aquino, 2020;Sim et al, 2020). Moreover, based on the recent research by Peters et al (unpublished;see also Peters, 2020), which showed that obsessing over daily coronavirus statistics might be counterproductive, we hypothesized that statistics stalking would be positively related to worry and panic buying.…”
Section: Affectmentioning
confidence: 94%
“…However, negative emotions such as fear or worry could also have negative consequences in case of dealing with a disaster. For example, previous research indicated that people experiencing fear and uncertainty (such as COVID-19 outbreak) tend to buy more things than usual (i.e., panic buying, Arafat et al, 2020;Lins and Aquino, 2020;Sim et al, 2020). Moreover, based on the recent research by Peters et al (unpublished;see also Peters, 2020), which showed that obsessing over daily coronavirus statistics might be counterproductive, we hypothesized that statistics stalking would be positively related to worry and panic buying.…”
Section: Affectmentioning
confidence: 94%
“…The researchers conducted a pilot study among 15 health professionals and 15 academics to explore issues with the understanding and operationalization of the scale, and minor modifications were made based on the feedback to ensure the ease comprehension of the items ( Lins & Aquino, 2020 ; Shammi et al, 2020 ). The estimated Cronbach’s alpha and composite reliability for government strategies and social distancing were 0.857 and 0.896 and 0.925 and 0.947, respectively, which are within the threshold limit ( Hair et al, 2014 , 2017 ).…”
Section: Methodsologymentioning
confidence: 99%
“…We refined the datasets using Microsoft Excel and screened data and generated estimates by running Smart PLS-SEM (SmartPLS-version 3) to examine the proposed hypotheses. SmartPLS-led structural equation modeling is a second-generation regression technique that uses a measurement model to assess the psychometric properties of scales ( Lins & Aquino, 2020 ) and a structural model to assess the hypothesized relationships ( Hair et al, 2017 ). Both measurement and structural models are indispensable parts of SEM.…”
Section: Methodsologymentioning
confidence: 99%
“…Individual factors : male sex ( 18 ); increased extraversion and neuroticism; low conscientiousness and openness ( 19 ); need to belong ( 20 ); need for safety or reassurance ( 21 23 ); anxiety or worry ( 8 , 21 , 23 ); reduced adherence to social distancing ( 17 ); conservative attitudes ( 17 );…”
Section: Introductionmentioning
confidence: 99%